BAMBOOS OF THE BATU PUTU BIODIVERSITY PARK LAMPUNG - Yeni Rahayu (Bioma, 2020)
Sumatra has a high diversity of bamboo (around 80 species of bamboo, and an unfinished record) in Indonesia. Lampung is one of the regions in Sumatra that has a great number of bamboo species and the endemic bamboos that has not been studied. The Batu Putu Biodiversity Park is an area designed by the local government to become Bamboo Education Tourism Center. Within a few years, the Batu Putu Biodiversity Park ecosystem can be changed effects a tourism activity. The exploratory study has been done to discover the bamboo species that originally grew in the Batu Putu Biodiversity Park, Lampung - Sumatra. The data that has been obtained from this study is important as a part of bamboo diversity data in Lampung, and Sumatra generally. Besides, it gave information about bamboo species that suitable to grow on the rocky soils. The result showed four genera, consisting of five species, namely Dendrocalamus asper, Gigantochloa atroviolacea, G. hasskarliana, Schizostachyum zollingeri, and Dinochloa sp. The last species is a candidate for a new record of Sumatran climbing bamboos, even new species candidates that we can not decide yet due to lack of samples and some particular conditions.